4x-4(-2x+1)=4-2(4x+24)

Simple and best practice solution for 4x-4(-2x+1)=4-2(4x+24) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 4x-4(-2x+1)=4-2(4x+24) equation:



4x-4(-2x+1)=4-2(4x+24)
We move all terms to the left:
4x-4(-2x+1)-(4-2(4x+24))=0
We multiply parentheses
4x+8x-(4-2(4x+24))-4=0
We calculate terms in parentheses: -(4-2(4x+24)), so:
4-2(4x+24)
determiningTheFunctionDomain -2(4x+24)+4
We multiply parentheses
-8x-48+4
We add all the numbers together, and all the variables
-8x-44
Back to the equation:
-(-8x-44)
We add all the numbers together, and all the variables
12x-(-8x-44)-4=0
We get rid of parentheses
12x+8x+44-4=0
We add all the numbers together, and all the variables
20x+40=0
We move all terms containing x to the left, all other terms to the right
20x=-40
x=-40/20
x=-2

See similar equations:

| y+13=772 | | 26-2x=-10 | | m+-494=418 | | u+39+46+u-4=180 | | -4v=860 | | -9(6+u)-3u=10 | | 8+z=39 | | c-18+2c-47+3c-49=180 | | 3x=-×1+80 | | 5m+3/4=2m-5 | | v12= -23 | | -9(+u)-3u=-10 | | 23w=322 | | r+153=-271 | | 868=-31g | | 3x=-×+80 | | 5x+50=x+14 | | 34+2b-12+b+8=180 | | 5x-3(2x-9)=2(3x-8)+9x | | 20 = y/31 | | 6x-44=2x+20 | | 20t+20+20t+20+20t+20=180 | | 20 = y31 | | 8x-12=5x+19 | | 9.444=u=4.333 | | 3/4(8x)-x=-3(x-7) | | y+302=773 | | (k+10)+(3k)=90 | | 2a—8a=12—8a | | 3x-5=3x+ | | -25y=-775 | | -11j=-385 |

Equations solver categories